Relationship between family history of type 2 diabetes and serum FGF21. (22nd September 2017) - Davis, Greggory R.; Deville, Tiffany; Guillory, Joshua; Bellar, David; Nelson, Arnold G.
Abstract: Background: Determining predictive markers for the development of type 2 diabetes (T2D), particularly in young individuals, offers immense potential benefits in preventative medicine. Previous research examining serum fibroblast growth factor 21 (FGF21) in humans has revealed equivocal relationships with clinical markers of metabolic dysfunction. However, it is unknown to what extent, if any, first‐degree family history of T2D (mother or father of the participant diagnosed with T2D) level affects serum FGF21 levels. The aim of this study was to determine whether in healthy individuals with FH+ ( n = 18) and without FH‐ ( n = 17) a family history of T2D affects serum FGF21. Materials and methods: Fasting serum and clinical, metabolic and anthropometric measures were determined using a cross‐sectional design. Results: Differences between groups for FGF21 were not significant (FH+ = 266 pg/mL ± 51·4, FH = 180 pg/mL ± 29; Z = 0·97, P = 0·33). Adiponectin values were lower in FH+ (8·81 μg/mL ± 2·14) compared to FH‐ (10·65 μg/mL ± 1·44; F = 8·83, P = 0·01). Resistin was negatively correlated with FGF21 for all participants ( r = −0·38, P = 0·03), but no other clinical, metabolic, or serum markers were predictive for serum FGF21 in FH+ or FH‐. Conclusions: Serum FGF21 is not significantly different between FH+ and FH‐ in young, healthy individuals. Based upon the data of this pilot study, it is unclear whether serum FGF21 can be used as a stand‐alone predictive marker for T2D in healthy subjects.